Hubungan Kualitas Tidur Dan Stres Dengan Tekanan Darah Lansia Di Desa Puton Kecamatan Diwek Kabupaten Jombang - Praningsih, Supriliyah; Siswati; Maryati, Heni; Priyanti, Ratna Puji (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: Hypertension is a disease that causes death silently or is called a silent killer. Many people with hypertension are not aware of the symptoms and problems that occur because there are no warning signs or symptoms (WHO, 2021). Risk factors that can affect the incidence of hypertension include sleep quality and stress. The purpose of this study was to determine the relationship between sleep quality and stress with blood pressure. Methods: This article design used correlational research with a